SISTEM PENDATAAN PELAKU UMKM BERBASIS WEB DI KOMITE PENGEMBANGAN EKONOMI KREATIF KABUPATEN MAJALENGKA - Arsyziyad, Mohammad Nushayr; Sujadi, Harun (Universitas Majalengka, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in regional economic growth and job creation, yet data collection in Majalengka remains largely manual, resulting in outdated and inconsistent information. This study aims to design and implement a web-based MSME data collection system at the Majalengka Creative Center to improve efficiency, accuracy, and accessibility of information. The system was developed using the Rapid Application Development (RAD) methodology, which emphasizes user involvement and iterative prototyping for faster and more adaptive development. The implementation utilized Next.js for the frontend and MongoDB as the database, enabling MSME actors to independently register, update, and manage their business profiles, while administrators can verify data, manage events, and generate statistical reports. Black-box testing with equivalence partitioning was conducted to evaluate functionality, with results showing that the system successfully supports registration, verification, and information dissemination processes, although some test cases revealed areas for improvement. Overall, the web-based system effectively reduces reliance on manual surveys, accelerates data validation, and enhances government capacity to deliver targeted training and assistance programs. This research demonstrates that digital solutions can strengthen transparency, optimize MSME empowerment, and support data-driven policy-making for sustainable local economic development.